2021
DOI: 10.1002/pro.4171
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of DNA supercoiling across evolution

Abstract: DNA supercoiling controls a variety of cellular processes, including transcription, recombination, chromosome replication, and segregation, across all domains of life. As a physical property, DNA supercoiling alters the double helix structure by under-or over-winding it. Intriguingly, the evolution of DNA supercoiling reveals both similarities and differences in its properties and regulation across the three domains of life. Whereas all organisms exhibit local, constrained DNA supercoiling, only bacteria and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 153 publications
(274 reference statements)
0
12
0
Order By: Relevance
“…SSBs induce the relaxation of DNA supercoils, leading to genome instability. 19 However, SSBs are efficiently repaired and inadequate to mediate the cytotoxic response. 20 As a SSB inducing agent, PtL is less toxic than CDDP, which was consistent with the results from the CCK-8 assay and cell cycle analysis.…”
Section: Resultsmentioning
confidence: 99%
“…SSBs induce the relaxation of DNA supercoils, leading to genome instability. 19 However, SSBs are efficiently repaired and inadequate to mediate the cytotoxic response. 20 As a SSB inducing agent, PtL is less toxic than CDDP, which was consistent with the results from the CCK-8 assay and cell cycle analysis.…”
Section: Resultsmentioning
confidence: 99%
“…DNA reverse gyrase and a high concentration of K + in microbial cells are important factors for maintaining the thermal stability of DNA molecules ( Duprey and Groisman, 2021 ). DNA molecules are easily subjected to double-strand breaks at high temperatures, so cells need some genes for DNA double-strand break repair, including dnaQ , holC , priA and ruvA ( Lenhart et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The type IIB Topo VI present in archaeal species is capable of relaxing both positive and negative supercoils, in addition to possessing decatenase activity [ 29 , 111 ]. The histone variants [ 112 ] and nucleoid-associated proteins (NAP) present can also constrain and modulate DNA supercoiling for regulation of DNA topology in Archaea [ 113 , 114 ] similar to NAPs in Bacteria [ 113 , 115 , 116 ], with mechanisms that may include direct stimulation of topoisomerase activities [ 117 , 118 , 119 , 120 ]. In the hyperthermophilic archaeon S. solfataricus , it was reported that homeostatic control of DNA supercoiling is mainly mediated by the fine-tuning of TopR1, one of the two reverse gyrases [ 121 ].…”
Section: Physiological Functions Of Type Ia Topoisomerasesmentioning
confidence: 99%